A, The Pengembangan Media Pembelajaran Aplikasi Sarana Belajar Prosedur pada Teks Prosedur Siswa Kelas XI Sekolah Menengah Atas Negeri 4 Tanjungpinang Tahun Pelajaran 2023/2024: Pengembangan Media Pembelajaran Aplikasi Sarana Belajar Prosedur pada Teks Prosedur Siswa Kelas XI Sekolah Menengah Atas Negeri 4 Tanjungpinang Tahun Pelajaran 2023/2024 - Ika Amelia Wati, Ika Amelia Wati; Harry Andheska, Harry Andheska; Asri Lolita, Asri Lolita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to develop learning media for Procedure Learning Tools Application on Procedure Text Material for Class XI Students of Senior High School Negeri 4 Tanjungpinang by measuring the validity and practicality levels of the developed media. The development model used in this research is the 4D model which starts from the defining stage, the design stage, to the development stage. The learning media developed in this study is an interactive media in the form of an application consisting of material and questions that must be completed to determine the ability of students to understand procedural text material. The procedure learning tool application was validated by two experts, namely, media experts and material experts. The number of students in the media practicality trial group is 5 students for the small group and 40 students for the large group. Data collection techniques The results of this study are media products Application of learning tools procedures with a percentage of validation from media experts reaching 87% with